Foreign bodies in adult upper digestive tract: a series of 30 cases - Jayaraman, Nirmal Kumar; V. J., Vikram; M., Kalaiselvi; M., Sudha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Rigid endoscopy under general anaesthesia has traditionally been used by otolaryngologist for diagnosis and management of variety of disorders affecting the upper digestive tract including the removal of foreign body. Smooth foreign bodies does not pose much threat but may cause airway obstruction. Sharp foreign bodies, if not removed the earliest may penetrate oesophageal wall and cause complications. Methods: A Retrospective analysis was done for patients who underwent rigid oesophaghoscopy under general anaesthesia for 30 patients of foreign body ingestion at Upgraded Institute of Otorhinolaryngology, Madras Medical College, Chennai, between November 2016 – November 2017. The records of age, sex, co-morbidities, X-ray finding, complications were recorded. Results: Majority of adults in this group belonged to 40-50 years age. The most common foreign body impacted was chicken bone totalling 16. 2 patients of denture ingestion were referred for flexible endoscopy after failed attempt, 1 developed oesophageal perforation. Conclusions: Rigid endoscopy is the gold standard for removal of sharp foreign body as the sharp ends can be clasped and brought in to the endoscope there by preventing damage to the mucosa. Foreign body with multiple sharp ends which cannot be negotiated into rigid endoscope, should be pushed into the stomach and attempted removal by cutting sharp ends of foreign body or by gastrostomy, as pulling such foreign body will lead to full length tear of oesophagus leading to morbidity and mortality.